The Dancers: The Insertion of a Monument into the Public Landscape through German Folk Dance - Kumm, Rosely (Revista do Colóquio, 2025)
This research is part of the studies conducted at the Laboratory for Extension and Research in Arts - LEENA/UFES, on public art in Espírito Santo state. It begins with the mediation of a public artwork entitled "The Dancers," created by the Espírito Santo artist Hipólito Alves, which serves as a memorial landmark and starting point for the creation of several German folk dance groups in the city of Domingos Martins, in the interior of the state of Espírito Santo. Considering the materiality of the monument and its immateriality as a cultural trait, this research analyzes how the artistic expression of German folk dance can intervene in the everyday landscape and symbolically reconfigure urban spaces through the performative presence of the body and cultural heritage. By being incorporated into public festivities, parades, squares, and community events, it was possible to observe that this cultural manifestation can contribute to the construction of meaning and the valorization of local public art.